Self-esteem, money attitude, credit card usage, and compulsive buying behaviour - Megawati Simanjuntak; Ambar Susan Rosifa (Universitas Islam Indonesia, 2016)
The study aims to analyze the impact of self-esteem, money attitude, and credit card usage behaviour on compulsive buying behaviour of working women. The study usescross sectional design with electronic survey methods (e-survey) involves 60 working women that use credit card. The Pearson correlation and multiple regression analysis are used as statistical tools. The result indicates that power prestige, anxiety, retention-time, and credit card usage behaviour significantly correlate to compulsive buying behaviour. Furthermore, compulsive buying behaviour is positively influenced by credit card usage behaviour. This paper suggests the Indonesian government to provide consumers education on aspects of financial planning and using credit card properly.